KECERNAAN KALSIUM DAN FOSFOR RANSUM KOMPLIT BERBASIS TEBON JAGUNG PADA TERNAK SAPI PERANAKAN ONGOLE (PO) - Koluod, Asuela A.; Kaunang, C.L.; Tuturoong, R.V.; Waani, M.R. (Universitas Sam Ratulangi, 2020)
DIGESTIBILITY OF CALCIUM AND PHOSPHORUS COMPLETE FEED BASED ON CORN FORAGE IN ONGOLE CROSSBREED COWS. Research was conducted to evaluate digestibility of calcium and phoshorus ongole crossbreed cows based on Corn Forage. Fourteen cows were used in this experiment, one and a half to two years old by weight of one hundred eighty to two hundred and fifty kilograms. this research was using experimental method, the data were analyzed by T test (Unequal Variance Assumed). Consisting of two replications and seven treatments used. The treatment used was : Ra = 50% concentrate+ 50% corn forage, Rb = 50% concentrate+ 25% king grass + 25% corn forage. The variables measured were feed calcium and phosphorus consumption, calcium and phosphorus digestibility. The results of analysis T test showed that intake capacity of calcium significantly affected (P<0.05) between Ra (31.49 gram/animal/day) and Rb (31.02 gram/animal/day) while calcium digestibility of treatment Rb (84.92%) higher significantly than Ra (77.70%). The results of analysis T test showed that intake capacity of phosphorus Rb (31.45 gram/animal/day) significantly affected (P<0.01) than Ra (30.52 gram/animal/day) and phosphorus digestibility Rb (88.39%) significantly affected (P<0.01) than Ra (83.94%). Based on the research result can be concluded that the complete feed consisting of 50% concentrate, 25% king grass (Pennisetum purpupoides) dan 25% corn forage increase digestibility of calcium and phosphorus ongole crossbreed cows.Key Words: Ongole crossbreed cattle, complete feed, digestibility, calcium and phosphorus.